Museum Object Lessons for the Digital Age - Geismar, Haidy (UCL Press, 2018)
Museum Object Lessons for the Digital Age explores the nature of digital objects in museums, asking us to question our assumptions about the material, social and political foundations of digital practices. Through four wide-ranging chapters, each focused on a single object - a box, pen, effigy and cloak - this short, accessible book explores the legacies of earlier museum practices of collection, older forms of media (from dioramas to photography), and theories of how knowledge is produced in museums on a wide range of digital projects. Swooping from Ethnographic to Decorative Arts Collections, from the Google Art Project to bespoke digital experiments, Haidy Geismar explores the object lessons contained in digital form and asks what they can tell us about both the past and the future. Drawing on the author's extensive experience working with collections across the world, Geismar argues for an understanding of digital media as material, rather than immaterial, and advocates for a more nuanced, ethnographic and historicised view of museum digitisation projects than those usually adopted in the celebratory accounts of new media in museums. By locating the digital as part of a longer history of material engagements, transformations and processes of translation, this book broadens our understanding of the reality effects that digital technologies create, and of how digital media can be mobilised in different parts of the world to very different effects.